THE USE OF MIMO-SYSTEMS FOR INCREASE RELIABILITY OF TELECOMMUNICATION SYSTEMS OF CRITICAL APPLICATION - Дрововозов, В. І.; Хемраєв, А .К. (Science-based technologies, 2009)
It is suggested to use communication networks on principle of MIMO for the increase of carrying capacity of wireless networks. For the decline of level of errors and increase of reliability of connection in the impulsive MIMO-system of critical application it is suggested to use the code of Alamouti.